DIDACTIC GAMES AS A MEANS OF DEVELOPING STUDENTS' MOTIVATION FOR COGNITIVE ACTIVITY - Ernazarova N. H. (Bright Mind Publishing, 2025)
This article discusses the task of increasing students' interest in mathematics through the use of gaming educational technologies. The expected learning outcomes of using didactic games are presented.
Keywords: Teaching mathematics, game, didactics, interest, mental development.